A comprehensive review of bibliometric and methodological approaches in flood mitigation studies: Current trends and future directions - Funmilayo Ebun Rotimi; Roohollah Kalatehjari; Taofeeq Durojaye Moshood; George Dokyi (Journal of Safety Science and Resilience)
Climate change has become a pressing concern, with an alarming increase in flooding events posing significant risks to residential areas worldwide. As land and infrastructure development rapidly evolve, it is crucial to systematically analyze the bibliometric patterns and methodological trends in flood mitigation research, with a specific focus on residential building flood mitigation. This study presents a comprehensive comparative analysis of the bibliometric patterns and methodological trends in flood mitigation research over the past two decades, identifies prevailing gaps, and proposes future research directions to enhance the effectiveness of flood mitigation strategies. Using data from the Scopus database, 441 publications were objectively selected and subjected to metadata analysis. The study identifies top authors, contributing institutions, nations, and the distribution of contributions across different fields and methodologies. The findings emphasize the need for an integrated and interdisciplinary approach to flood reduction research, considering the complex interplay of social, ecological, and physical dimensions in flood risk management. The study reveals the predominance of modeling and simulation approaches, geographic information systems (GIS) remote sensing approaches, and statistical and data-driven approaches as the most widely employed methodologies. Furthermore, it highlights the growing diversity of approaches, with increasing interest in machine learning algorithms and combined methods. Also, this study provides valuable recommendations for future research, emphasizing the importance of developing effective flood-mitigating strategies to enhance community resilience. It advocates for a multidisciplinary and integrated approach, leveraging geospatial technologies, machine learning algorithms, and collaborative methodologies to advance flood mitigation research and practice. Future research should consider exploring additional databases, including Web of Science, EBSCO, IEEE, and Google Scholar, to conduct a more comprehensive review of the available literature. There is need for future studies to conduct in-depth comparative analyses of flood mitigation methodologies, particularly in the context of residential buildings.